PENGARUH SOSIALISASI PAJAK, TINGKAT PEMAHAMAN PAJAK, KESADARAN PAJAK, DAN PERSEPSI WAJIB PAJAK MENGENAI PERATURAN PAJAK TERHADAP KEPATUHAN PELAPORAN PAJAK (Studi Empiris pada Wajib Pajak Orang Pribadi Pelaku UMKM yang Terdaftar di KPP Pratama Semarang Candisari Periode Tahun 2021-2024) - Sekarputih Hayuningtyas; Imam Ghozali (Diponegoro Journal of Accounting, 2026)
This study aims to examine the effect of tax socialization, tax understanding, tax awareness, and perception of tax regulations on tax reporting compliance of individual taxpayers (WPOP) among MSMEs at KPP Pratama Semarang Candisari. This research employs a quantitative approach using primary data collected through questionnaires distributed to 126 respondents selected using purposive sampling. The data analysis methods include instrument testing (validity and reliability), classical assumption tests, multiple linear regression analysis, t-test (partial), F-test (simultaneous), and coefficient of determination (R²). The results show that partially, tax understanding and tax awareness have a positive and significant effect on tax reporting compliance. Meanwhile, tax socialization and perception of tax regulations do not have a significant effect on tax reporting compliance. Simultaneously, all independent variables have a significant effect on tax reporting compliance. The coefficient of determination (Adjusted R Square) is 0.517, indicating that 51.7% of the variation in tax reporting compliance can be explained by the variables in this study, while the remaining 48.3% is influenced by other factors outside the model.